Oesophageal-pleural fistulation identified through repeated malpositioning of nasogastric tubes. (16th August 2018) - Cheetham, Laura Josephine; Mitchell, Edwin
Abstract : Two previously fit and healthy males with acute onset dyspnoea and respiratory failure required invasive ventilation for respiratory failure. Insertion and correct positioning of nasogastric tubes (NGT) proved to be difficult repeatedly in both cases over the course of a number of days. Repeated imaging found NGT tips sited in varied, atypical positions including extension into the hemithoraces. Delineation of repeated malpositioned NGTs identified oesophageal perforations in the case of both patients, one with fistulation into the right pleura and the other into the left pleura. Both patients developed an empyema ipsilateral to the side of fistulation. Both patients died, with subsequent postmortems concluding one patient to have experienced a spontaneous out-of-hospital oesophageal perforation, and the second patient's perforation developing as a consequence of a distal oesophageal squamous cell carcinoma. These two cases highlight the importance of questioning the possibility of underlying oesophageal pathology promptly if repeated NGT insertions are unsuccessful or imaging reveals unusual transit paths of NGTs.